The Effect of Electronic Nursing Documentation (END) Implementation on Nursing Services Toward Patients’ Satisfaction - Halimatussakdiah, H; Faisal, T. Iskandar; Nuraskin, Cut Aja; Ahmad, Aripin; Alhuda, Alhuda (Universitas Aisyah Pringsewu, 2022)
Services in nursing are developing nowadays, one of which is the documentation of nurses’ performance by means of computers. Documentation of nursing services is carried out 24 hours for inpatients. The complex and continuous workload of nurses in service requires tools that support their work to create professional service documentation. This study aims to examine the design of the nursing care documentation model using a computer including assessment, nursing diagnosis, planning, implementation and evaluation. The variables tested in this study were patients’satisfaction, nurses’performance, syar'i ethics and the Electronic Nursing Documentation (END) program. A quantitative designed were used with a cross-sectional approach. The samples were 420 patients. Respondent was obtained through multistage sampling. The independent variable was the surgical patient with criteria aged 17-50 years, postoperative day 2-3, no complications, the patient was conscious, could read and write and was willing to be a respondent. The dependent variable was nurses’ performance and patients’ satisfaction. Data collection was performed using a questionnaire and was analyzed with SEM version 22. The results of this study indicated that nurses can provide comprehensive nursing care for patients by using digital documentation (Electronic Nursing Documentation application). The use of Electronic Nursing Documentation (END) can increase patients’ satisfaction through syar'i ethics and good nurses’ performance. Of all the variables tested in model development, syar'i ethics affect improved patients’ satisfaction.SEM test results obtained GFI (Goodness of Fit Index) values which should be within the expected Cut of Value range (p-Value less than 0.05). The use of END in nursing services and supported by syar'i ethics and proper nurses’ performance can increase patients’ satisfaction post-surgery. Abstrak: Pelayanan keperawatan telah berkembang saat ini, salah satunya adalah pendokumentasian kinerja perawat melalui komputer. Pendokumentasian pelayanan keperawatan dilakukan 24 jam untuk pasien rawat inap. Beban kerja perawat yang kompleks dan berkesinambungan dalam pelayanan membutuhkan alat yang mendukung pekerjaannya untuk membuat dokumentasi pelayanan yang profesional. Penelitian ini bertujuan untuk mengkaji rancangan model dokumentasi asuhan keperawatan dengan menggunakan komputer meliputi pengkajian, diagnosa keperawatan, perencanaan, implementasi dan evaluasi. Variabel yang diuji dalam penelitian ini adalah kepuasan pasien, kinerja perawat, etika syar'i dan program Electronic Nursing Documentation (END). Rancangan penelitian yang digunakan adalah kuantitatif dengan pendekatan cross-sectional. Sampel sebanyak 420 pasien. Responden diperoleh melalui multistage sampling. Variabel bebas adalah pasien bedah dengan kriteria usia 17-50 tahun, hari ke 2-3 pasca operasi, tidak ada komplikasi, pasien sadar, dapat membaca dan menulis dan bersedia menjadi responden. Variabel terikat adalah kinerja perawat dan kepuasan pasien. Pengumpulan data dilakukan dengan menggunakan kuesioner dan dianalisis dengan SEM versi 22. Hasil penelitian ini menunjukkan bahwa perawat dapat memberikan asuhan keperawatan yang komprehensif kepada pasien dengan menggunakan dokumentasi digital (aplikasi Electronic Nursing Documentation). Penggunaan Electronic Nursing Documentation (END) dapat meningkatkan kepuasan pasien melalui etika syar'i dan kinerja perawat yang baik. Dari semua variabel yang diuji dalam pengembangan model, etika syar'i berpengaruh terhadap peningkatan kepuasan pasien. Hasil uji SEM diperoleh nilai GFI (Goodness of Fit Index) berada dalam rentang Cut of Value yang diharapkan (p Value 0,05). Penggunaan END dalam pelayanan keperawatan dan didukung dengan etika syar'i dan kinerja perawat yang baik dapat meningkatkan kepuasan pasien pasca operasi.